Listening Comprehension Skills: Storytelling Method among Third-Grade Students at Primary School - Narti Ohoibor; Sarah Sahetapy; Ribka L. Ririhena (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The listening skills of third-grade students at Primary School II Latihan SPG Ambon were initially suboptimal. This study aims to enhance these skills through the storytelling method. Employing a Classroom Action Research (CAR) design, the study was conducted over two cycles involving 28 students (15 boys and 13 girls). Data collection techniques included observation, tests, and interviews to ensure a comprehensive evaluation of student progress. The findings demonstrate a consistent and significant improvement across all research phases. The classical mean score rose from 62.42 in the pre-test to 67.85 in Cycle I, ultimately reaching 77.42 in Cycle II. More impressively, the student completion rate increased dramatically from 23.8% in the pre-test to 100% by the end of the second cycle, surpassing the established success indicators. Analytical results highlight that the most substantial growth occurred in the character understanding dimension, which saw a 50.7% increase, driven by the teacher's expressive delivery and narrative gestures. The study concludes that the storytelling method is highly effective in creating an engaging, imaginative, and meaningful learning environment. Consequently, it is recommended as an innovative, student-centered instructional approach to improve listening comprehension and literacy foundations in lower primary school grades.